Ultrahigh-heat-conductivity corrosion-resistant magnesium alloy and preparation method thereof

By adding elements such as Zn, Ce, La, Sm and Ca to the magnesium alloy, and using graded rolling and annealing treatment, an ultra-high thermal conductivity and corrosion resistance magnesium alloys are prepared, which solves the shortcomings of existing magnesium alloys in terms of heat dissipation and corrosion resistance, and achieves a comprehensive improvement of high thermal conductivity, strength and corrosion resistance.

CN119571160APending Publication Date: 2025-03-07CHANGSHA ADVANCED MATERIALS IND RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839859.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The application of existing magnesium alloys in the field of heat dissipation is limited by their thermal conductivity and corrosion resistance, and it is difficult to meet the comprehensive needs of high strength, high thermal conductivity and corrosion resistance.

Method used

Using the Mg-Zn-Ca-RE alloy system, an ultra-high thermal conductivity and corrosion-resistant magnesium alloy was prepared by adding 4.5~5.5 wt.% Zn, 0.3~0.5 wt.% rare earth elements such as Ce, La, Sm and 0.05~0.1 wt.% Ca, combined with graded rolling and annealing treatment.

Benefits of technology

It has achieved high thermal conductivity (108~113W/(m·K)), high strength (208~218MPa) and excellent corrosion resistance of magnesium alloys, and is suitable for the thermal conductivity, heat dissipation and lightweight requirements in aerospace, weapons and equipment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571160A_ABST
    Figure CN119571160A_ABST
Patent Text Reader

Abstract

The invention provides an ultrahigh heat conduction and corrosion resistance magnesium alloy and a preparation method thereof. The ultrahigh heat conduction and corrosion resistance magnesium alloy is an Mg-Zn-Ca-RE alloy system. Wherein RE is a rare earth element, the content of RE is 0.3-0.5 wt.%, the content of Zn is 4.5-5.5 wt.%, the content of Ca is 0.05-0.1 wt.%, and the balance is Mg and unremovable impurities. RE is at least one of La, Ce and Sm. According to the preparation principle, smelting, semi-continuous casting, annealing, extrusion cogging and graded rolling treatment are carried out, and the ultrahigh-heat-conduction corrosion-resistant magnesium alloy with high strength, high heat conduction performance and excellent corrosion resistance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloys, and in particular to an ultra-high thermal conductivity and corrosion-resistant magnesium alloy and a preparation method thereof. Background Art

[0002] With the development of intelligence and integration, the demand for heat dissipation in electronic products is becoming more and more urgent; with the further development of 5G communication and even the development of 6G technology in the future, the demand for heat dissipation in the communication industry, intelligent manufacturing and other fields will become more urgent. As the lightest metal structural material at present, magnesium alloy has the advantages of light weight, good thermal conductivity and heat dissipation performance and electromagnetic shielding performance, and has very good application potential in the field of heat dissipation. The thermal conductivity of pure magnesium is 157 W / (m·K), but its yield strength is below 70 MPa, which is difficult to meet the mechanical performance requirements of industrial applications. Among the commonly used magnesium alloys, ZK61 with the best thermal conductivity is only 90-110 W / (m·K), but its thermal conductivity is only 57%~70% of pure magnesium, which does not give full play to the thermal conductivity of magnesium alloys, limiting the wide application of magnesium alloys in the field of heat dissipation. In order to meet the needs of the heat dissipation field and cater to the development trend of lightweight, the development of ultra-high thermal conductivity magnesium alloy materials and their preparation processes has a very good promotion significance for promoting the industrial application of magnesium alloys.

[0003] The corrosion rate of magnesium alloys is directly related to their durability and service life. A higher corrosion rate means that magnesium alloys are more likely to corrode quickly under specific conditions, thereby reducing their structural integrity and affecting their reliability in engineering applications. Therefore, when using magnesium alloys in engineering applications, it is necessary to consider the corrosion rate of magnesium alloys in specific application scenarios. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an ultra-high thermal conductivity and corrosion-resistant magnesium alloy and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: On the one hand, the present invention provides an ultra-high thermal conductivity and corrosion-resistant magnesium alloy, wherein the ultra-high thermal conductivity and corrosion-resistant magnesium alloy is a Mg-Zn-Ca-RE alloy system; wherein RE is a rare earth element, and its content is 0.3-0.5wt.%, Zn content is 4.5-5.5wt.%, Ca content is 0.05-0.1wt.%, and the balance is Mg and non-removable impurities; The RE is at least one of La, Ce, and Sm.

[0006] On the other hand, the present invention provides a method for preparing the above-mentioned ultra-high thermal conductivity and corrosion-resistant magnesium alloy, comprising the following steps: S1. Prepare raw materials according to the proportion of elements; S2, preheating the raw materials, melting them under a protective atmosphere, and performing semi-continuous casting after cooling to obtain magnesium alloy cast rods; S3, lathe the magnesium alloy cast rod, saw cut it and then perform homogenization annealing treatment; S4, extruding the annealed magnesium alloy cast rod into a blank to obtain a magnesium alloy blank; S5, performing graded rolling on the magnesium alloy billet to obtain a rolled plate; S6. heat treating the rolled plate.

[0007] Preferably, in step S2, the protective atmosphere is N 2 With SF 6 Mixed gas or CO 2 With SF 6 of mixed gases.

[0008] Preferably, in step S2, the preheating temperature is 150-300°C.

[0009] Preferably, the smelting in step S2 and the semi-continuous casting after cooling are specifically performed as follows: First, pure Mg is melted at 700-720°C, and then pure Zn is added to melt at the same temperature and stirred thoroughly; then the melt temperature is increased to 740-780°C, Mg-Ca intermediate alloy is added to melt, and stirred with pure Ar gas for 5-15 minutes, and then Mg-RE intermediate alloy is added to melt, and stirred with pure Ar gas for 10-30 minutes, wherein the Ar gas flow rate is 10-25L / s; after stirring, the mixture is kept at 740-780°C for 20-30 minutes, and then the temperature is lowered, and semi-continuous casting is started when the temperature drops to 690-710°C.

[0010] Preferably, in step S3, the homogenization annealing treatment is specifically performed as follows: Heat the magnesium alloy casting rod to 200~250℃ and keep it for 1~1.5h, then increase the temperature to 380~420℃ and keep it for 15~20h.

[0011] Preferably, in step S4, the temperature of the extrusion blanking is 330-360° C., and the extrusion ratio ER is ≥8.

[0012] Preferably, in step S5, the specific operation of the graded rolling to obtain the rolled plate is: The magnesium alloy cast rod after extrusion is firstly subjected to the first stage multi-pass rolling at 360~400℃ to a thickness of b 1 The pass reduction is 10-25%, and the heat preservation between passes is 30-60 minutes; then the second stage multi-pass rolling is carried out at 150-300℃ to a thickness of b 0, and obtain a rolled plate, the pass reduction is 2-8%, and the insulation between passes is 5-15 minutes; the obtained rolled plate is water-cooled to obtain the rolled plate; wherein, b 0 is the target thickness of the rolled plate, .

[0013] Preferably, in step S6, the specific operation of the heat treatment is: Anneal the rolled plate at 150-200°C for 2-6 hours.

[0014] Compared with the prior art, the beneficial technical effects of the present invention are as follows: The present invention adds Zn to the magnesium alloy, because Zn has good solid solubility in the magnesium alloy, and the solid solubility of Zn in the magnesium alloy changes greatly with temperature, so Zn has the effect of solid solution strengthening and heat treatment strengthening on the magnesium alloy; adding Zn to the magnesium alloy can improve the solubility of the impurities that cannot be removed in the magnesium alloy, thereby improving the thermal conductivity and corrosion resistance of the magnesium alloy. Moreover, the "specific thermal resistivity" and "specific resistivity" of Zn in the magnesium alloy (i.e., the increase in thermal resistivity and resistivity caused by adding one atomic percentage of solute atoms) are the smallest, so the present invention chooses to add 4.5~5.5wt.% of Zn, which can not only ensure that the magnesium alloy has higher mechanical properties, but also has less effect on the thermal conductivity of the magnesium alloy.

[0015] 0.3~0.5wt.% of any one or at least two rare earth elements among Ce, La, Sm are added to the magnesium alloy. Since the above rare earth elements are more likely to react with gases and impurities in the melt, the impurity and gas content in the magnesium alloy is reduced, thereby improving the thermal conductivity and corrosion resistance of the magnesium alloy. At the same time, the above rare earth elements are easy to form a second phase with magnesium alloy elements and precipitate at the grain boundary, which has a good pinning effect on the grain boundary, making the grains finer and more uniform, and enhancing the mechanical properties and corrosion resistance of the alloy.

[0016] Adding 0.05~0.1 wt.% Ca to magnesium alloy can improve the oxidation resistance of magnesium alloy melt, reduce the possibility of oxidation during smelting and casting, achieve the effect of purifying the melt, and improve the thermal conductivity and corrosion resistance of magnesium alloy formed by the purified melt; on the other hand, Ca can form Mg 2 Ca can improve the mechanical properties of magnesium alloys, and the addition of Ca has little effect on the thermal conductivity of magnesium alloys.

[0017] The present invention adopts a graded rolling method, performs the first-stage multi-pass rolling at 360-400°C, controls the heat preservation position between passes to be 30-60min, and the pass reduction is 10-25%, so that the grains deformed by rolling are fully recovered and recrystallized, and at the same time, there will be slight grain growth after the grains are recovered, so that the grains of the plate rolled by the first stage multi-pass rolling are uniform and the grain size is relatively large. Perform the second stage multi-pass rolling at 150-300°C, control the heat preservation position between passes to be 5-15min, and the pass reduction is 2-8%. During the second stage multi-pass rolling, the deformation amount of the rolled plate from the surface to the core (the center line of the thickness direction of the rolled plate) gradually decreases, so the surface grains of the rolled plate rolled by the second stage multi-pass rolling are fine, and the core grains are relatively large. The larger the grains, the better the thermal conductivity of the alloy; the finer the grains, the more favorable the mechanical properties of the alloy, and the finer the grains, the more uniform the grain structure, the more uniform the energy difference and electrode potential difference between the grain boundary, and the better the corrosion resistance of the material. The present invention obtains a rolled plate with a gradient structure of fine surface grains and larger core grains through graded rolling, which can take into account the mechanical properties, corrosion resistance and thermal conductivity of the alloy at the same time, and is conducive to the comprehensive improvement of high strength, high thermal conductivity and corrosion resistance. The rolled plate after rolling is subjected to water cooling treatment to eliminate deformation stress and improve the thermal conductivity, corrosion resistance and mechanical properties of the magnesium alloy. Finally, the present invention performs low-temperature and short-time annealing treatment on the rolled plate obtained by rolling to reduce the influence of deformation stress and dislocation on thermal conductivity and corrosion resistance, and at the same time, it can prevent the grains from recovering and recrystallizing and growing, thereby ensuring that the magnesium alloy has good mechanical properties.

[0018] The ultra-high thermal conductivity and corrosion-resistant magnesium alloy provided by the present invention has a thermal conductivity of 108-113 W / (k·m), a tensile yield strength of 208-218 Mpa, a tensile strength of 291-306 Mpa, an elongation of 7-9%, and an immersion hydrogen evolution corrosion rate of 3.3-3.6 mm / y; it has high strength, high thermal conductivity and excellent corrosion resistance. It can provide high-quality magnesium alloy materials for the heat conduction, heat dissipation and lightweight requirements of new equipment and new processes in the fields of aerospace, weapons and equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0020] Figure 1 This is a graph showing the results of an immersion hydrogen evolution experiment provided by an embodiment, wherein Figure 1 (a) is the result of the immersion hydrogen evolution experiment of Example 1, Figure 1(b) is the result of the immersion hydrogen evolution experiment in Example 2. Figure 1 (c) is the result of the immersion hydrogen evolution experiment in Example 3. Figure 1 (d) is the result of the immersion hydrogen evolution experiment of Comparative Example 1. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1 The smelting process of magnesium alloy is 2 +SF 6 The process is carried out under the protective atmosphere of 200℃. Before smelting, pure Mg, pure Zn, Mg-Ce master alloy and Mg-Ca master alloy are fully preheated at 200℃. Pure Mg is first melted at 720℃, pure Zn is melted at this temperature, and fully stirred. Then the melt temperature is raised to 750℃, Mg-Ca master alloy is first added at this temperature, and high-purity Ar gas is used to stir it after it is fully dissolved. The stirring time is 10min, and then Mg-Ce master alloy is added. After it is fully melted, high-purity Ar gas is used to stir it for 15min, and the Ar gas flow rate is 15L / s. After stirring, it is kept at 750℃ for 25min, and then the temperature is lowered. When the temperature drops to 700℃, semi-continuous casting is started to prepare high thermal conductivity magnesium alloy casting rods. The semi-continuous casting method prepares φ320mm Mg-4.6Zn-0.3Ce-0.08Ca magnesium alloy ingots. The surface was removed by machining, and the product was homogenized by keeping the temperature at 380℃ for 18h. The φ320×100mm cast rod was forged and blanked at 380℃. After blanking, the 20×200×300mm billet was graded and rolled. First, it was rolled to a thickness of 12.3mm at 360℃ for 3 passes, with a reduction of 15% per pass and 35min between passes; then it was rolled to a thickness of about 10.4mm at 250℃ for 2 passes, with a reduction of 8% per pass and 25min between passes; after rolling, the plate was quickly water-cooled; then it was annealed at 200℃ for 2h to obtain the Mg-4.6Zn-0.3Ce-0.08Ca alloy.

[0023] Example 2 The smelting process of magnesium alloy is 2 +SF 6The process is carried out under a protective atmosphere. Before smelting, pure Mg, pure Zn, Mg-Sm master alloy and Mg-Ca master alloy are fully preheated at 200℃. Pure Mg is first melted at 720℃, pure Zn is melted at this temperature, and fully stirred. The melt temperature is then raised to 750℃, at which the Mg-Ca master alloy is first added, and after it is fully dissolved, it is stirred with high-purity Ar gas for 10 minutes. Then, the Mg-Sm master alloy is added, and after it is fully melted, it is stirred with high-purity Ar gas for 15 minutes. The Ar gas flow rate is 15L / s. After stirring, it is kept at 750℃ for 20 minutes, and then the temperature is lowered. When the temperature drops to 690℃, semi-continuous casting is started to prepare high thermal conductivity magnesium alloy casting rods. The semi-continuous casting method prepares φ320mm Mg-5Zn-0.2Sm-0.05Ca magnesium alloy ingots. The surface was removed by machining, and the product was homogenized by keeping it at 400℃ for 10h. The φ320×100mm cast rod was forged and blanked at 360℃. After blanking, 25×200×300mm billets were taken for graded rolling. First, they were rolled to a thickness of 16.6mm at 380℃ for 2 passes, with a reduction of 19% per pass and a 45min insulation between passes; then, they were rolled to a thickness of about 15mm at 200℃ for 2 passes, with a reduction of 5% per pass and a 20min insulation between passes; after rolling, the plate was quickly water-cooled; then, it was annealed at 180℃ for 4h to obtain the Mg-5Zn-0.2Sm-0.05Ca alloy.

[0024] Example 3 The smelting process of magnesium alloy is 2 +SF 6The process is carried out under a protective atmosphere. Before smelting, pure Mg, pure Zn, Mg-(La / Ce) mixed rare earth master alloy and Mg-Ca master alloy are fully preheated at 200°C. Pure Mg is first melted at 720°C, pure Zn is melted at this temperature, and fully stirred. The melt temperature is then raised to 750°C, at which the Mg-Ca master alloy is first added, and after it is fully dissolved, it is stirred with high-purity Ar gas for 10 minutes. Then, Mg-Ce master alloy and Mg-Ce master alloy are added, and after they are fully melted, they are stirred with high-purity Ar gas for 20 minutes, and the Ar gas flow rate is 15L / s. After stirring, the temperature is kept at 750°C for 25 minutes, and then the temperature is lowered. When the temperature drops to 700°C, semi-continuous casting is started to prepare high thermal conductivity magnesium alloy casting rods. A φ320mm magnesium alloy ingot of Mg-5.5Zn-0.4 (Ce / La) -0.03Ca was prepared by semi-continuous casting. The surface was removed by machining, and the ingot was homogenized by keeping at 400℃ for 8h. The φ320×100mm cast rod was forged and blanked at 340℃. After blanking, a 21×200×300mm billet was graded and rolled. First, it was rolled to a thickness of 9mm at 400℃ for 3 passes, with a reduction of 25% per pass and 60min between passes; then it was rolled to a thickness of about 8mm at 300℃ for 4 passes, with a reduction of 3% per pass and 25min between passes; after rolling, the plate was quickly water-cooled; then it was annealed at 150℃ for 10h to obtain Mg-5.5Zn-0.4 (Ce / La) -0.03Ca alloy.

[0025] Comparative Example 1 The semi-continuous casting method was used to prepare the φ320mm ZK61 (Mg-5.4Zn-0.4Zr-0.1Mn) magnesium alloy ingot. After machining to remove the skin and homogenization treatment, the φ320×100mm billet was forged and opened. After opening, the 20×200×300mm billet was graded and rolled. First, it was rolled to a thickness of 12.3mm at 380℃ for 3 passes, with a reduction of 15% per pass and 360min between passes; then it was rolled to a thickness of about 10.4mm at 350℃ for 2 passes, with a reduction of 8% per pass and 25min between passes; after rolling, the plate was quickly water-cooled; then annealed at 180℃ for 6h to obtain the Mg-5.4Zn-0.4Zr-0.1Mn alloy.

[0026] Comparative Example 2 The semi-continuous casting method was used to prepare the φ320mm Mg-3.4Zn-0.4Zr-0.1Mn magnesium alloy ingot. After machining to remove the skin and homogenization treatment, the φ320×100mm billet was taken for forging and blanking. After blanking, the 20×200×300mm billet was taken for graded rolling. First, it was rolled to a thickness of 12.3mm at 380℃ through 3 passes, with a pass reduction of 15% and a heat preservation of 360min between passes; then it was rolled to a thickness of about 10.4mm at 350℃ through 2 passes, with a pass reduction of 8% and a heat preservation of 25min between passes; after rolling, the plate was quickly water-cooled; then annealed at 200℃ for 2h to obtain the Mg-3.4Zn-0.4Zr-0.1Mn alloy.

[0027] Comparative Example 3 The smelting process of magnesium alloy is 2 +SF 6 The process is carried out under a protective atmosphere. Before smelting, pure Mg, pure Zn, Mg-Ce master alloy and Mg-Ca master alloy are fully preheated at 200℃. Pure Mg is first melted at 720℃, pure Zn is melted at this temperature, and fully stirred. The melt temperature is then raised to 750℃, at which the Mg-Ca master alloy is first added, and after it is fully dissolved, it is stirred with high-purity Ar gas for 10 minutes. Then, the Mg-Ce master alloy is added, and after it is fully melted, it is stirred with high-purity Ar gas for 15 minutes. The Ar gas flow rate is 15L / s. After stirring, it is kept at 750℃ for 25 minutes, and then the temperature is lowered. When the temperature drops to 700℃, semi-continuous casting is started to prepare high thermal conductivity magnesium alloy casting rods. The semi-continuous casting method prepares φ320mm Mg-4.6Zn-0.3Ce-0.08Ca magnesium alloy ingots. The surface was removed by machining, and the product was homogenized by keeping the temperature at 380℃ for 18h. The φ320×100mm cast rod was forged and blanked at 380℃. After blanking, the 20×200×300mm billet was graded and rolled. The billet was first rolled to a thickness of 10.5mm at 360℃ in 4 passes, with a reduction of 15% per pass and 35min of insulation between passes. After rolling, the plate was quickly water-cooled. Then, the plate was annealed at 200℃ for 2h to obtain the Mg-4.6Zn-0.3Ce-0.08Ca alloy.

[0028] As shown in Table 1, Table 1 shows the experimental results of thermal conductivity, tensile test and immersion hydrogen evolution test of Examples 1-3 and Comparative Examples 1-3.

[0029] Table 1 Thermal conductivity and tensile test results

[0030] Where λ is the thermal conductivity; δ bis the tensile strength; δ 0.2 is the tensile yield strength; δ is the elongation.

[0031] It can be seen from the table that the thermal conductivity, tensile strength, tensile yield strength and elongation of Examples 1-3 are all improved compared with those of Comparative Example 1, indicating that the ultra-high thermal conductivity and corrosion-resistant magnesium alloy provided by the present invention has high strength and high thermal conductivity.

[0032] As for Example 1 and Comparative Example 3, there is only a difference in the graded rolling method. From the data in Table 1, it can be seen that the thermal conductivity, tensile strength and elongation of Example 1 are all higher than those of Comparative Example 3; the immersion hydrogen evolution corrosion rate of Example 1 is lower than that of Comparative Example 3; this is because in the preparation process of Example 1, in addition to the first-level multi-pass rolling as described in Comparative Example 3, a second-level multi-pass rolling is performed after the first-level multi-pass rolling, and the temperature is controlled to be 250°C, the pass reduction is 8%, and the pass insulation is 25 minutes, so that the surface grains of the rolled plate after the second-level multi-pass rolling are fine, and the core grains are relatively large, so that the alloy prepared by it has both mechanical properties, corrosion resistance and thermal conductivity. Therefore, the magnesium alloy prepared by the process described in the present invention has high strength, high thermal conductivity and excellent corrosion resistance.

[0033] Zr is added in Comparative Example 2. As can be seen from Table 1, compared with Examples 1-3, the tensile strength and tensile yield strength of Comparative Example 2 are lower than those of Examples 1-3, and the immersion hydrogen evolution corrosion rate of Comparative Example 2 is higher than that of Examples 1-3. This is because the density difference between Zr and Mg is very large, which easily leads to gravity segregation, thereby affecting the performance of the prepared alloy. In addition, the Zn content in Comparative Example 2 is 3.4%. Since the solid solubility of Zn in magnesium alloys varies greatly with temperature, and the addition temperature of Zr is generally 780°C, the addition of Zr will weaken the solid solution strengthening and heat treatment strengthening effects of Zn on magnesium alloys, thereby preventing the mechanical properties and corrosion resistance of magnesium alloys from being better.

[0034] The 168h immersion hydrogen evolution experiment was carried out on Examples 1-3 and Comparative Examples 1-3. The experimental results are shown in Table 1. It can be seen that the immersion hydrogen evolution corrosion rate of Comparative Example 1 is the highest, which is 5.73mm / y; the immersion hydrogen evolution corrosion rate of Example 1 is the lowest, which is 3.38mm / y. Compared with Comparative Examples 1-3, the immersion hydrogen evolution corrosion rates of Examples 1-3 are lower than those of Comparative Examples 1-3.

[0035] Reference Figure 1 , Figure 1The results of the immersion hydrogen evolution experiments of Comparative Example 1 and Examples 1-3 are shown. It can be seen from the figure that the surface morphology of the sample of Example 1 is the best; the surface morphology of the sample of Comparative Example 1 is rough and granular, with obvious corrosion marks; and the surface morphology of the samples of Examples 2 and 3 is also better than that of Comparative Example 1. It can be seen that the ultra-high thermal conductivity and corrosion-resistant magnesium alloy provided by the present invention has excellent corrosion resistance.

[0036] Matters not covered by the present invention are known technologies.

[0037] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0038] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ultra-high thermal conductivity and corrosion-resistant magnesium alloy, characterized in that: The ultra-high thermal conductivity and corrosion-resistant magnesium alloy is a Mg-Zn-Ca-RE alloy system; wherein RE is a rare earth element with a content of 0.3-0.5 wt.%, Zn content of 4.5-5.5 wt.%, Ca content of 0.05-0.1 wt.%, and the balance is Mg and non-removable impurities; The RE is at least one of La, Ce, and Sm.

2. The method for preparing the ultra-high thermal conductivity and corrosion-resistant magnesium alloy according to claim 1, characterized in that: The following steps are involved: S1. Prepare raw materials according to the proportion of elements; S2, preheating the raw materials, melting them under a protective atmosphere, and performing semi-continuous casting after cooling to obtain magnesium alloy cast rods; S3, lathe the magnesium alloy cast rod, saw cut it and then perform homogenization annealing treatment; S4, extruding the annealed magnesium alloy cast rod into a blank to obtain a magnesium alloy blank; S5, performing graded rolling on the magnesium alloy billet to obtain a rolled plate; S6. heat treating the rolled plate.

3. The preparation method according to claim 2, characterized in that: In step S2, the protective atmosphere is a mixed gas of N2 and SF6 or a mixed gas of CO2 and SF6.

4. The preparation method according to claim 2, characterized in that: In step S2, the preheating temperature is 150-300°C.

5. The preparation method according to claim 2, characterized in that: The specific operation of smelting in step S2 and performing semi-continuous casting after cooling is as follows: First, pure Mg is melted at 700-720°C, and then pure Zn is added to melt at the same temperature and stirred thoroughly; then the melt temperature is raised to 740-780°C, Mg-Ca master alloy is added to melt, and pure Ar gas is used to stir for 5-15 minutes, and then Mg-RE master alloy is added to melt, and pure Ar gas is used to stir for 10-30 minutes, wherein the Ar gas flow rate is 10-25 L / s; After stirring is completed, keep the temperature at 740~780℃ for 20~30min, then start cooling, and start semi-continuous casting when the temperature drops to 690~710℃.

6. The preparation method according to claim 2, characterized in that: In step S3, the homogenization annealing treatment is specifically performed as follows: Heat the magnesium alloy casting rod to 200~250℃ and keep it for 1~1.5h, then increase the temperature to 380~420℃ and keep it for 15~20h.

7. The preparation method according to claim 2, characterized in that: In step S4, the temperature of the extrusion process is 330-360° C., and the extrusion ratio ER is ≥8.

8. The preparation method according to claim 2, characterized in that: In step S5, the specific operation of the graded rolling to obtain the rolled plate is: The magnesium alloy cast rod after extrusion is firstly subjected to a first-stage multi-pass rolling at 360-400°C to a thickness of b1, with a pass reduction of 10-25%, and a heat preservation period of 30-60 minutes between passes; then, a second-stage multi-pass rolling is performed at 150-300°C to a thickness of b0 to obtain a rolled plate, with a pass reduction of 2-8%, and a heat preservation period of 5-15 minutes between passes; the obtained rolled plate is water-cooled to obtain the rolled plate; wherein b0 is the target thickness of the rolled plate, .

9. The preparation method according to claim 2, characterized in that: In step S6, the specific operation of the heat treatment is: Anneal the rolled plate at 150-200°C for 2-6 hours.